Local Culture as a Mediating Variable in the Relationship Between Destination Image and Tourists’ Visit Intention in Madura Raya - Raden Khaeru Ahmadi; Siti Sa'adah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine the role of culture in mediating the relationship between destination image and tourists’ intention to visit tourism destinations in Madura Raya. A quantitative approach was employed using a survey method involving tourists who have knowledge of or interest in tourism destinations in Madura Raya. The data were analyzed using regression analysis and mediation testing. The findings reveal that destination image has a positive and significant effect on tourists’ visiting intention as well as on culture. Culture also has a positive and significant effect on visiting intention. Furthermore, culture partially mediates the relationship between destination image and visiting intention. These results highlight the strategic role of culture in strengthening the influence of destination image on tourists’ intention to visit. Therefore, tourism development in Madura Raya should integrate destination branding strategies with the preservation and promotion of local culture to achieve sustainable and competitive tourism development.